A stamp technique to restore central incisor dentinal tooth body - G. Dolce (LLC "Endo Press", 2022)
This case report describes palatal wall direct restoration with the stamp technique in Twenty-eight-year-old patient. The procedure was completed with the silicone index, transparent silicon and composite resin. After 5 years function patients was satisfied with the obtained functional result and had a wish to improve the adjacent tooth aesthetics.